2021
DOI: 10.3390/ijerph18189663
|View full text |Cite
|
Sign up to set email alerts
|

Transcultural Adaptation and Validation of the Spanish Version of the Sexual Satisfaction Scale for Women (SSS-W-E)

Abstract: Background: Sexual satisfaction is a complex and multidimensional concept. It encompasses physical, emotional, relational and cultural dimensions, and constitutes an essential component of sexual health, as well as an indicator of quality of life and wellbeing. The Sexual Satisfaction Scale for Women (SSS-W) was designed in the United States, and it is a valid and reliable tool to measure women’s sexual satisfaction. Aim: The aim of this study was to culturally adapt and translate the SSS-W into Spanish and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…After reading the titles and applying the selection criteria to the complete documents, 13 articles and a total of 15 questionnaires were selected [ 8 , 14 , 15 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…After reading the titles and applying the selection criteria to the complete documents, 13 articles and a total of 15 questionnaires were selected [ 8 , 14 , 15 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Four questionnaires have been identified that assess QoL [ 8 , 14 , 26 , 30 ], five of them measure the impact of PFD on sexual function [ 15 , 25 , 28 , 29 , 32 ], seven evaluate the symptoms of POP and UI [ 8 , 14 , 25 , 26 , 27 , 30 , 31 ], and one was focused on pregnant women [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations